Proiectul „LibHub – biblioteci deschise și incluzive” - CIORBA, Natalia (BIBLIOPOLIS, 2025)
The project “LibHub – Open and Inclusive Libraries” was implemented by the Mihail Lomonosov Library during 2024-2025, offering tailored services to Ukrainian refugees and migrants. Activities included digital skills training for seniors, Romanian language classes for adults, and a visual programming and robotics club for children. The project aimed to foster social integration through education, emotional support, and personal development. It demonstrated the library’s potential as a space of inclusion and community support, providing a replicable model of best practices for similar institutions.